The Claim of Fragmented Self in Autobiography of Red by Anne Carson - Talei, Leila (eTopia, 2016)
This paper offers a discursive reading of the Autobiography of Red (1998) written by Anne Carson, a novel loosely based on the myth of Geryon and the Tenth Labor of Herakles. Carson’s Geryon is a fragmented modern subject who is molested as a child and betrayed in a love affair as an adult. At one of its thematic levels the work examines the efforts of an outcast who attempts to reclaim a meaningful subjectivity in a modern world characterized by fragmentation grounded in anxieties, frenetic confusion, and cultural pressures. The term “fragmentation” has a multiplicity of meanings and changes its signi - cance depending on the individual/subjective sociocultural context. The study of the formation of a fragmented self must take into account the variety of factors, including class, gender and cultural frameworks. This paper interrogates such symbiotic relationships between the processes of subject fragmentation within a social realm and the principles and values introduced by the power structures apparent within society. Referring to Michel Foucault’s Discipline and Punish, where discipline “makes” individuals in the society and is the technique used by the dominant power to control its subjects as instruments, this paper examines the connection between Carson’s novel and the notion of agency within fragmentation. By portraying a sexually disoriented subject, Carson shows how power structures are formed and manipulated through its agents (Geryon’s mother, brother and Herakles), and offers an illustration of the alternatives available to those who resist being framed. I examine the portrayals of such subjects’ striving for liberation from the hierarchies of power through the intertextual embodiment of the image of an eruptive volcano and its generative power of wrath which resists to be categorized or tamed by “Mother Nature.” This paper evaluates the essential features and outcomes of the myth of Geryon as a study of a fragmented subject struggling to bring the fissuring dimensions of his personality and sexuality together to form an autonomous subjectivity. KEYWORDS: Subjectivity, Fragmentation, Power Principle, Body, Individuality Norms